Hubungan antara Persiapan Guru PJOK dan Kualitas Pembelajaran Jasmani di Sekolah Dasar : Kajian Literatur Review (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to analyze the relationship between the readiness of Physical Education, Sports, and Health (PJOK) teachers and the quality of physical education learning in elementary schools through a Systematic Literature Review (SLR) approach. The study was conducted by analyzing 25 national and international articles published between 2015–2025, using the PRISMA guide to ensure a systematic data selection and analysis process. The results show that teacher readiness, especially in pedagogical and professional aspects, has a significant influence on the effectiveness of physical education learning. Teachers who have high readiness tend to create an active, enjoyable learning atmosphere and focus on the holistic development of students. Conversely, limited training, facilities, and institutional support are inhibiting factors in improving the quality of learning. This study emphasizes the importance of improving teacher readiness through continuous professional training and adequate school environmental support to realize quality physical education learning in elementary schools.